Elevated cholesterol among African American adults: the role of fatalistic attitudes about health. Issue 6 (17th August 2020) - de Dios, Marcel A.; Childress, Sarah D.; Cano, Miguel Ángel; McNeill, Lorna H.; Reitzel, Lorraine R.; Vaughan, Ellen
ABSTRACT: Objectives: Cardiovascular disease (CVD) affects 47% of African-American adults (AAs) in the United States. Elevated cholesterol, the greatest risk factor for CVD, is highly prevalent among AAs, potentially as the result of engagement in behavioral risk factors. Religiosity has been associated with a beneficial effect in health promoting behaviors, yet findings have been mixed depending on methods employed. Religious health fatalism, defined as 'the belief that health outcomes are inevitable and/or determined by God', is a more specific domain of a religiosity that needs further exploration through scientific research. The purpose of the current study is to examine the relationship between RHFQ subscales and self-reported lifetime history of elevated cholesterol. Methods: Participants ( n  = 135) were recruited from a large, predominately African American church. A multiple logistic regression model was used to test whether the three subscales of the Religious Health Fatalism Questionnaire (RHFQ) were cross-sectional predictors of self-reported lifetime history of elevated cholesterol. Sets of variables were entered into a stepwise logistic regression model with the first set (Block 1) including significant demographic variables and religiosity (i.e. sex, age, level of education, employment status and scores on the Lukwago Religiosity Scale score [LRS]. The three RHFQ subscales were entered into Block 2 as our predictors of interest. Results: After adjusting for covariates, the likelihood of elevated cholesterol increased significantly (OR = 3.21, 95% CI = 1.81–5.69, p  < .001) as Helpless Inevitability (RHFQ subscale) scores increased. Conclusions: A greater degree of Helpless Inevitability was found to be significantly associated with self-reported elevated cholesterol level. Future research is needed to further understand the complex interplay of factors associated with religiosity and fatalism that contribute to increased risk of elevated cholesterol among AAs.